KAJIAN IMPLEMENTASI KEBIJAKAN DAN DAMPAK E-BUDGETING DALAM MEWUJUDKAN GOOD GOVERNANCE - ghaliyah nimassita triseptya; Arifuddin Arifuddin; Rahmawati Rahmawati (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
This study aims to examine the implementation of e-budgeting policies and their impact on realizing the principles of good governance within regional government institutions. The method employed is library research through a systematic review of scholarly journals, books, official reports, and other relevant academic documents. The findings indicate that the adoption of e-budgeting enhances transparency, accountability, efficiency, and effectiveness in public budget management. The system strengthens internal control mechanisms through electronic recording, automated reporting, real-time monitoring, and clearer audit trails. The integration of e-planning and e-budgeting has also been shown to improve coordination among government units and reduce opportunities for budget irregularities. Nevertheless, the effectiveness of its implementation is highly influenced by organizational governance, bureaucratic culture, and the integrity of public officials. Overall, e-budgeting serves as a strategic instrument for reinforcing good governance and increasing public trust in regional financial management.